CONVERGENCE OF THE RESULTS OF INTERPRETATION REMOTE METHOD WITH FIELD WORK ON A LINEAR OBJECT. ON THE EXAMPLE OF LANDSLIDE PLOT - Maxim Yu. Baborykin (Izvestiâ Tomskogo politehničeskogo universiteta. Inžiniring georesursov, 2020)
The article discusses the technology of airborne laser scanning used to study the topography, geomorphology and mapping of dangerous geological processes with the description required in the regulatory documents, as well as comparison of the forecast data of the remote method for determining the slip mirror compared with geophysical and geological research methods. The aim ofthe study is to obtain positive statistics on using the method of interpretation of hazards geological processes using airborne laser scanning combined with digital aerial photography; to compare the forecast data of the surface of rupture with the classical geological and geophysical studies of the landslide area and, as a result, reveal the reliability of using the interpretation method. Object: section of the slope of the project pipeline layout. The subject is gravitational geological processes, their form, state and activity. Methods: direct method of interpretation. Since laser scanning of a terrain allows obtaining an array of laser reflection points from the ground surface in the presence of vegetation, the direct method of interpretation allows determining the boundaries and textural features of landslides. Traditional research methods, geodetic survey of the area, drilling of wells, geophysical studies, etc. were used. Results. Comparison of the remote method and field studies showed a fairly high convergence in identification of landslides (the boundaries of bodies and their appearance). Determination of the proposed surface of rupture landslide in appearance for an assessment in front of the field also shows the convergence of results sufficient for an assessment when choosing competitive areas.World experience gained in the field of application of aerometodes in surveys shows their exceptional efficiency. Thus, the method is effective for making design decisions before field research, and also eliminates the possibility of under-exploration of the territory immediately before the start of field research.